Exploring the Bibliometric Landscape of Biodiversity Finance: Integrating Nature into Financial Risk Assessment - Judijanto, Loso; Nurhasanah, Dila Padila; Novitasari, Salwa Aulia (Westscience Press, 2025)
The accelerating biodiversity crisis has prompted a paradigm shift in the financial sector, where integrating nature into financial risk assessment is becoming increasingly vital. This study conducts a comprehensive bibliometric analysis to explore the intellectual landscape of biodiversity finance, focusing on how biodiversity is being incorporated into financial theory, investment practices, and sustainability governance. Using the Scopus database and VOSviewer software, the study analyzes co-occurrence networks, temporal trends, density visualizations, and collaboration patterns among authors, institutions, and countries. The findings reveal that “biodiversity,” “finance,” and “sustainable finance” serve as conceptual anchors, while emerging themes such as “decentralized finance,” “green bonds,” and “ESG” indicate growing innovation in the field. The United Kingdom and United States lead global collaborations, with strong linkages to European and Asian institutions. This research contributes theoretically by clarifying the field’s multidimensional evolution and practically by identifying knowledge gaps and strategic entry points for policy, investment, and academic advancement. Limitations include database coverage and lack of qualitative content analysis, suggesting future research directions. Overall, the study underscores the critical role of interdisciplinary collaboration in advancing biodiversity-aligned financial systems.